ICYMI: RT and Youth-Oriented International Broadcasting as (Geo)Political Culture Jamming. (July 2022) - Saunders, Robert A; Crilley, Rhys; Chatterje-Doody, Precious N
Research in political communication has recently begun to explore the role of non-Western English-language state-funded international broadcasters (NEIBs) in influencing international audiences. Despite this, there has been little attention given to understanding how NEIBs engage and influence young people in 'Western' democracies. Our article addresses this gap by providing a detailed analysis of RT's English-language, youth-orientated news product ICYMI. Launched in 2018, ICYMI is a social media-based news brand that consists of a series of 2–3-min videos that deliver satirical takes on recent global events including military conflict, financial scandals, and culture clashes. Our findings, which examine the first year of the platform's activity, show that ICYMI is a novel form of engagement, one that is not easily categorised as either public diplomacy or propaganda, nor can it be described as traditional journalism. Instead, we label this approach as geopolitical culture jamming. In this article, we conduct a discourse analysis of 45 videos published on YouTube by ICYMI over its first year to examine how the platform attempts to influence how young people relate to traditional foreign policy discourses. Our empirical analysis centres on how viewers engage with and interpret ICYMI's videos with the aim of addressing how RT may be influencing younger audiences, particularly its core demographic of Anglophone white males whose comments reflect an attachment to ICYMI's populist, anti-elite worldview.